Aripiprazole for the treatment of Tourette syndrome. (3rd April 2021) - Cox, Joanna H.; Cavanna, Andrea E.
ABSTRACT: Introduction : Tourette syndrome (TS) is a neurodevelopmental disorder characterized by multiple tics which often persisting in forms of different severity throughout adult life. The prevalence of neuropsychiatric co-morbidity in patients with TS is high. Treatment of TS can involve pharmacological, behavioral, or, in rare cases, surgical therapies. Over the last two decades there has been growing interest in the use of aripiprazole, a novel partial dopamine receptor agonist, as a promising anti-tic agent. Areas covered : The authors reviewed the available literature evaluating the role of aripiprazole in the treatment of TS and other tic disorders in both children and adults. This includes data from five randomized controlled trials (RCTs) and eleven open-label studies. Expert opinion : There is moderate quality evidence supporting the use of aripiprazole in reducing tic severity in children and adolescents, however there is a lack of robust evidence evaluating its use in adults, despite expert consensus. Overall, it appears that aripiprazole is a safe and effective treatment for tics. Further large scale RCTs assessing the long-term efficacy and safety of aripiprazole in the treatment of tics are warranted, especially in adult populations with TS.